Understanding media violence and the development of aggressive behavior of school children - Kong, Luo Lan; Abdullah, Maria Chong; Roslan, Samsilah (Elsevier, 2010)
Aggressive behaviour among school children had raised a cause of concern in Malaysia. The development of aggressive behaviour places children at serious risk for future mal-adaptation in the form of continued aggression, conduct problems, and overall difficulties in the domain of social relationships. Therefore, there is a need to study the origins and development of aggressive behaviour. This paper focuses on the nature of aggressive behaviour among school children, the theories that underlying the aggressive behaviour, and the impact of media violence on the development of aggressive behaviour of school children.